Advokasi dan Komunikasi dalam Pencegahan Penyebaran Berita Hoax untuk Meningkatkan Literasi Digital oleh Dinas Komunikasi dan Informatika Provinsi Sumatera Barat - Saza Rahmanda; Afriva Khaidir (PUBLICNESS: Journal of Public Administration studies, 2022)
This research departs from public literacy in understanding the validity of news is still low, people's habits to disseminate information (share) without seeking the truth. This type of research is qualitative with descriptive method, in this study the author uses purposive sampling methods and techniques while the technique used to test the validity of the data is by using triangulation techniques. The results of this study are (1) Implementation of advocacy programs to improve digital literacy by the Department of Communication and Information of West Sumatra Province, a. advocacy through cooperation, advocacy through supervision. (2) Implementation of communication programs to improve digital literacy by the Department of Communication and Information of West Sumatra Province, a. advocacy and communication through socialization, b. communication through the anti-hoax movement. 3. Factors influencing advocacy and communication in preventing the spread of hoax news by the Communications and Information Office of West Sumatra Province, a. inhibiting factors, and b. supporting factors.